Motivation Strategies to Improve Learners’ Participation and Performance. - Haufiku, Isidor; Shoopala, Tresia (Journal of Multidisciplinary Research and Development, 2025)
The main purpose of this study was to explore the motivation strategies to enhance Secondary School learners’ participation and performance in Mathematics in Elim circuit in the Omusati Region, Namibia. The study used a case study qualitative research design. Data were collected using interview, Observation and documents analysis. Twenty participants (20) (consisted of 3 principals and 17 teachers) were purposefully selected from 3 schools in Elim Circuit in the Omusati Region. The study revealed that most teachers and principals in the study area they motivate learners through intrinsic motivation by give them positive feedback, teachers enthusiasm in their work and learners as well as extrinsic motivation by giving them a token of appreciation, financial rewards and awarding the certificate of best performing or most improved learners. The study recommended that teachers in Elimi Circuit should plan and make their lesson interesting by integrating technology, build confidence of learners, prioritise group work, teachers should be resourceful and they should continue to combine intrinsic and extrinsic motivation strategies when motivating the learners.